Analisis risiko dalam berinvestasi pada reksadana saham di Bursa Efek Indonesia - Harahap, Ghilman Rozy (FEBI IAIN Langsa, 2022)
Investment risk is what may happen to an investor that occurs due to unsatisfactoryinvestment returns. There are many kinds of investment risks, such as interest, businessand other risks. Mutual funds are alternative investments or diversified investments forinvestors who want to invest with capital. limited. Mutual funds have small risks and goodreturns, so that mutual fund investments have many advantages for investors. Thisresearcher has the main objective to calculate and analyze the level of profit and level ofrisk in protected mutual funds. The purpose of this study is to know the risks of investingin mutual funds on the stock exchange. The type of data used in this study is secondarydata. To achieve the research objectives, the first method used is to calculate the return ofprotected mutual funds, calculate risk in the form of standard deviation of protectedmutual funds, and the selection of protected mutual funds with optimal risk and return.